2007
DOI: 10.1101/gr.6316407
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the vertebrate ancestral genome reveals dynamic genome reorganization in early vertebrates

Abstract: Although several vertebrate genomes have been sequenced, little is known about the genome evolution of early vertebrates and how large-scale genomic changes such as the two rounds of whole-genome duplications (2R WGD) affected evolutionary complexity and novelty in vertebrates. Reconstructing the ancestral vertebrate genome is highly nontrivial because of the difficulty in identifying traces originating from the 2R WGD. To resolve this problem, we developed a novel method capable of pinning down remains of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
460
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(506 citation statements)
references
References 34 publications
39
460
1
1
Order By: Relevance
“…According to previous studies, the ancestor of teleosts had 24 chromosomes, and chromosomal fission/fusion may have occurred in fishes with various chromosome numbers (Kasahara et al 2007;Nakatani et al 2007). Among the five cyprinids investigated, bighead carp, silver carp and grass carp all retained the ancestral chromosome number in their haploid genome (n = 24), while zebrafish (n = 25) and common carp (n = 50) did not.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the ancestor of teleosts had 24 chromosomes, and chromosomal fission/fusion may have occurred in fishes with various chromosome numbers (Kasahara et al 2007;Nakatani et al 2007). Among the five cyprinids investigated, bighead carp, silver carp and grass carp all retained the ancestral chromosome number in their haploid genome (n = 24), while zebrafish (n = 25) and common carp (n = 50) did not.…”
Section: Discussionmentioning
confidence: 99%
“…In their in silico reconstructions of ancestral vertebrate chromosomes, neither Nakatani et al (2007) nor Kohn et al (2006) specifically addressed the question of ancestral synteny of amniote sex chromosomes, but their proposed ancestral karyotypes do not recover synteny of snake with bird, or bird with mammal, sex chromosomes. The absence of ancestral synteny in the blocks that make up the sex chromosomes of extant therian mammals, birds, and snakes suggests that they were each derived independently from different ancestral autosomes.…”
Section: Sex Chromosomes In Amniotesmentioning
confidence: 99%
“…Further afield, teleost fish such as Gasterosteus, Danio, Fugu, and Oryzias also provide an appropriate outgroup, but they are not ideal because the teleost genome duplication complicates detection of orthologs (Kasahara et al 2007) and their genomes are rearranged and gene duplicates have dropped out, so synteny is poorly conserved (Nakatani et al 2007). However, fine-scale analysis of these genomes produced no evidence of synteny of bird Z and human X orthologs in teleost fish .…”
Section: Sex Chromosomes In Amniotesmentioning
confidence: 99%
“…Vertebrates usually have two highly conserved CRH receptors (CRHR1 and CRHR2) that arose by gene duplication in the two rounds of basal vertebrate genome doubling (Cardoso et al 2014), the so-called 1R and 2R events (Nakatani et al 2007, Putnam et al 2008. The ancestor of teleost fish went through a third round of genome doubling called 3R (Jaillon et al 2004) that generated a duplicate of the crhr1 gene, leading to Crhr1a and Crhr1b, which were only retained in a few species (Cardoso et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A paralogon is a set of related chromosomes or chromosome regions, usually resulting from a tetraploidization. Vertebrate paralogons typically have four chromosome members in each paralogon as a consequence of the two tetraploidizations (1R and 2R) (Nakatani et al 2007, Putnam et al 2008, and as many as eight members in teleost fish due to their third tetraploidization (3R) (Jaillon et al 2004). Hwang and coworkers suggested that the two ancestral CRH/UCN1 and UCN2/UCN3 precursor genes arose before the vertebrate tetraploidizations and ended up on separate chromosomes, whereupon each chromosome was quadrupled in the tetraploidizations, but only two peptide genes survived in each paralogon resulting in the four peptide genes that were included in their study, (Figure 4 in Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 99%